2018
DOI: 10.17765/1983-1870.2017v10n3p587-596
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas De Avaliação Precoce Na Identificação De Morbidades Maternas: Revisão Sistemática

Abstract: O objetivo desse trabalho foi identificar, por meio de uma revisão sistemática, os sistemas de avaliação precoce existentes que são aplicados às gestantes, descrevendo os parâmetros vitais utilizados, as semelhanças\diferenças, bem como a efetividade desses instrumentos. Trata-se de um estudo de revisão sistemática, cujas pesquisas foram realizadas utilizando as bases de dados MEDLINE, SciELO, LILACS, BIREME e PubMed sendo encontrados 191 artigos. Excluíram-se os artigos que não tinham como foco o estudo, rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…[4] As a result, some physiological changes in vital signs that can occur during pregnancy in young/healthy patients end up hindering the early recognition of clinical decompensation, since these patients have a good response to pathological mechanisms. [11] Edwards, Dore, Van Schalkwyk and Armson (2020) observed in their study that there was a period for the occurrence of physiological deterioration in patients with severe morbidity, and although this event happens slowly and progressively, it ends up going unnoticed. and/or is treated inappropriately.…”
Section: Insertion Of the Modified Obstetric Warning Scoring System (...mentioning
confidence: 98%
See 1 more Smart Citation
“…[4] As a result, some physiological changes in vital signs that can occur during pregnancy in young/healthy patients end up hindering the early recognition of clinical decompensation, since these patients have a good response to pathological mechanisms. [11] Edwards, Dore, Van Schalkwyk and Armson (2020) observed in their study that there was a period for the occurrence of physiological deterioration in patients with severe morbidity, and although this event happens slowly and progressively, it ends up going unnoticed. and/or is treated inappropriately.…”
Section: Insertion Of the Modified Obstetric Warning Scoring System (...mentioning
confidence: 98%
“…Therefore, when performing the patient assessment, he follows a reassessment pattern according to the presented score score or following specific standardized measures. [11] Tuyishime, et al (2020) state that this system is not a system that will define the treatment of pregnant women, but it is a tool that will assist in the early recognition of deteriorating women. Therefore, Shuler et al (2019) found that in a sample of 83% of patients who were classified as high obstetric risk, 49% of them had abnormalities in physiological parameters, demonstrated by changes in MEOWS scores.…”
Section: Insertion Of the Modified Obstetric Warning Scoring System (...mentioning
confidence: 99%
“…Com isso, algumas mudanças fisiológicas nos sinais vitais, que podem ocorrer na gestação em pacientes jovens/saudáveis, acabam dificultando o reconhecimento precoce de descompensação clínica, uma vez que essas pacientes apresentam boa resposta frente aos mecanismos patológicos 8 .…”
Section: Inserção Do Sistema De Pontuação De Advertência Obstétrica M...unclassified
“…Edwards , Dore, Van Schalkwyk e Armson observaram em seu estudo, que existia um período para a ocorrência da deterioração fisiológica em pacientes que apresentam morbidade grave, e por mais que esse evento aconteça de forma lenta e progressiva, ele acaba passando despercebido e/ou é tratado de forma inadequada. Segundo alguns autores, os sinais de anormalidade geralmente podem ser detectados em até oito horas antes aos eventos desfavoráveis acontecerem, como internação em UTI e parada cardiorrespiratória [6][7][8][9][10][11][12] .…”
Section: Inserção Do Sistema De Pontuação De Advertência Obstétrica M...unclassified
See 1 more Smart Citation